Rigid pi-bridge construction strategy thermally activated delayed fluorescent material and application thereof

CN119431253AActive Publication Date: 2025-02-14LIANYUNGANG TECHN COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411560178.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

在构建红色TADF发射段时,所选片段的3LE态通常远高于它们的CT能级(1CT和3CT),使它们无法影响RISC,虽然最近才发现某些大的熔融芳香A段的三线态能级在红色TADF发射段所需的范围内,但并非所有这些大的熔融芳香A段都是如此,当它们被用于构建橙色/红色TADF发射器时,它们的3LE状态可能有助于改善kRISC然而,具有类似电子吸出能力的A段可能在其3LE能级上显示出显着差异,然而,决定这些差异的原因尚未阐明,因此,迫切需要进行深入的分析,以揭示它们,并进一步制定设计高效TADF发射器的标准

Benefits of technology

[0016] (1) In the present invention, using pyrene quinoxaline as the conjugated π bridge, connecting the cyanobenzene acceptor (A) unit and triphenylline (TPA) donor (D) unit, and constructing a suzuki coupling with a having a A new TADF material with D-A molecular structure TPA-PyQl-BzCN is a new TADF material constructed by large conjugated π bridge unit. It is used in the molecular construction of thermally activated delayed fluorescent materials, providing a thermally activated delayed fluorescent material. A new construction strategy has expanded the types of organic near-infrared luminescent materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431253A_ABST
    Figure CN119431253A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of organic electroluminescent materials, and particularly discloses a thermally activated delayed fluorescent material based on a rigid pi-bridge construction strategy and application thereof, and the thermally activated delayed fluorescent material is prepared by taking pyrenequinoxaline as a conjugated pi bridge to connect a cyanobenzene acceptor (A) unit and a triphenylamine (TPA) donor (D) unit, the preparation method comprises the following steps: constructing a structure of a novel TADF material TPA-PyQl-BzCN with a D-A molecular structure through suzuki coupling; pyrene quinoxaline is used as a conjugated pi bridge, a cyanobenzene acceptor (A) unit and a triphenylamine (TPA) donor (D) unit are connected, a novel TADF material TPA-PyQ l-BzCN with a D-A molecular structure is constructed through suzuki coupling, and the TADF material is a brand-new TADF material constructed by a large conjugated pi bridge unit, is used for molecular construction of a thermally activated delayed fluorescent material, and has a wide application prospect. A new construction strategy is provided for thermally activated delayed fluorescent materials, and the variety of organic near-infrared luminescent materials is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic electroluminescent materials, and in particular relates to a thermally activated delayed fluorescent material using a rigid π-bridge construction strategy and an application thereof. Background Art

[0002] Thermally activated delayed fluorescence emitters, also known as TADF emitters, are highly desirable for use in organic light-emitting diodes (OLEDs) because they have the potential to achieve 100% internal quantum efficiency (IQE) compared to pure organic fluorophores. The transition from triplet excited states to singlet states, which undergoes anti-intersegment crossing (RISC), is essential;

[0003] This is because RISC is an important factor in determining the use of triplet excitons, and therefore the rate constant corresponding to it (k RISC ) must be appropriately increased. Theoretically, (k RISC ) is proportional to ΔEst, where and ΔEst are the energy gaps between the spin-orbit coupling (soc) matrix elements and the singlet (S) and triplet (T) excited states, respectively. or reducing ΔEst may help improve the final k RISC Many early studies have shown that ΔEst can be easily reduced by using highly twisted electron donor (D)-electron acceptor (A) type molecular designs. This has been demonstrated by many different research groups. This is because such a geometry is able to limit the overlap between the highest occupied molecular orbitals (HOMOs) and the lowest unoccupied molecular orbitals (LUMOs), thereby reducing ΔEst during the charge transfer (CT) transition;

[0004] On the other hand, in this pure CT singlet state ( 1 CT) and triplet ( 3 CT) may become closer and closer to zero, which completely violates the principle of accelerating k RISC Fortunately, there is a straightforward answer to this puzzle, which is to tune the energy level arrangement and guide the local excited triplet state ( 3 CT) state to promote the RISC process. This has been shown to successfully solve the problem;

[0005] So far, several TADF molecules have been reported to have 6 s -1 K RISC value. Since these emitters 3 The energy levels of the LE state are very close to 1 CT / 3The energy level of the CT state is thus significantly contributed to the improvement of the RISC process. 3 LE states are usually much higher than their CT levels ( 1 CT and 3 CT), making them unable to affect RISC. Although it has only recently been discovered that some large fused aromatic A segments have triplet levels in the range required for red TADF emitters, this is not the case for all of these large fused aromatic A segments. When they are used to construct orange / red TADF emitters, their 3 The LE state may contribute to the improvement of kRISC, however, the A segment with similar electron-sucking ability may be 3 Significant differences are shown in the LE energy levels; however, the reasons that determine these differences have not been elucidated, and thus, in-depth analyses are urgently needed to reveal them and further develop criteria for designing efficient TADF emitters. Summary of the invention

[0006] The purpose of the present invention is to provide a thermally activated delayed fluorescent material with a rigid π-bridge construction strategy and its application, so as to solve the problems raised in the above background technology.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A thermally activated delayed fluorescent material with a rigid π-bridge construction strategy, comprising: using pyrenequinoxaline as a conjugated π bridge, connecting a cyanobenzene acceptor (A) unit and a triphenylamine (TPA) donor (D) unit, and constructing a new TADF material TPA-PyQl-BzCN with a DA molecular structure through Suzuki coupling. The specific molecular structure is shown below:

[0009]

[0010] Preferably, TADF luminescent material, TPA-PyQl-BzCN as the luminescent layer dopant, and CBP as the main material are used to manufacture the luminescent layer through spin coating and heating annealing process.

[0011] Preferably, a doped TADF organic electroluminescent device is prepared to obtain a TADF organic electroluminescent device with an emission peak of 564 nm and an EQE of 7.2%.

[0012] Preferably, the structure of the TADF organic electroluminescent device is:

[0013] ITO / PEDOT:PSS(35nm) / PVK(30nm) / EML(35nm) / TmPyPB(45nm) / LiF(0.5nm) / Al(120nm);

[0014] Among them, PVK is the hole transport layer, TmPyPB is the electron transport layer, PEDOT:PSS is the hole injection layer, EML is the light-emitting layer, which is a mixture of the guest material TPA-PyQl-BzCN and the host material (4,4'-di(9-carbazole)biphenyl), and the cathode layer is composed of lithium fluoride and aluminum.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] (1) In the present invention, pyrenequinoxaline is used as a conjugated π bridge to connect a cyanobenzene acceptor (A) unit and a triphenylamine (TPA) donor (D) unit, and a new TADF material TPA-PyQl-BzCN with a DA molecular structure is constructed through Suzuki coupling. This is a new TADF material constructed with a large conjugated π bridge unit and is used in the molecular construction of thermally activated delayed fluorescent materials. It provides a new construction strategy for thermally activated delayed fluorescent materials and expands the types of organic near-infrared luminescent materials.

[0017] (2) Compared with the common TADF materials constructed with phenanthroquinoxaline conjugated π-bridge units, it has a stronger spin coupling constant (SOC), smaller root mean square deviation (RMSD) and higher quantum yield (PLQY).

[0018] (3) Through simple and reasonable molecular construction, it has a high-position anti-gap crossing channel, and its quantum yield PLQY is as high as 90%, which has the ability to be solution-processed electroluminescent devices.

[0019] (4) The molecular structure is simple, easy to synthesize, and the preparation cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The UV-visible absorption spectra of the compounds TPA-PyQl-BzCNT and TPA-PhTh-BzCN prepared in Example 1 of the present invention in toluene;

[0021] Figure 2 The photoluminescence spectra of the compounds TPA-PyQl-BzCNT and TPA-PhTh-BzCN prepared in Example 1 of the present invention in toluene solution;

[0022] Figure 3 The photoluminescence spectra of the compounds TPA-PyQl-BzCNT and TPA-PhTh-BzCN prepared in Example 1 of the present invention in the thin film;

[0023] Figure 4 CV spectra of compounds TPA-PyQl-BzCNT and TPA-PhTh-BzCN prepared in Example 1 of the present invention;

[0024] Figure 5 The theoretical calculation spectra of the compounds TPA-PyQl-BzCNT and TPA-PhTh-BzCN prepared in Example 1 of the present invention;

[0025] Figure 6 The low temperature fluorescence phosphorescence and lifetime spectra of the compounds TPA-PyQl-BzCNT and TPA-PhTh-BzCN prepared in Example 1 of the present invention;

[0026] Figure 7 Device correlation diagrams of compounds TPA-PyQl-BzCNT and TPA-PhTh-BzCN prepared in Example 1 of the present invention;

[0027] Figure 8 This is the synthesis route of the target compounds TPA-PyQl-BzCNT and TPA-PhTh-BzCN of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1: Synthesis of TADF luminescent materials TPA-PyQl-BzCNT and TPA-PhTh-BzCN Figure 8 As shown;

[0030] Synthesis of compound M1

[0031] In a round-bottom flask, pyrene (10.00 g, 49.50 mmol, 1.0 eq.) and RuCl 3 ·xH 2 O (1.23 g, 4.74 mmol, 0.096 eq.) was dissolved in 200 mL of acetonitrile. 4 (42.75 g, 198 mmol, 4.0 eq.) was dissolved in 100 mL of hot water and carefully added to the pyrene solution. Then 100 mL of DCM was added and stirred vigorously at room temperature;

[0032] The reaction mixture was stirred for 18 h. The suspension was filtered through Celite, and the filtrate was extracted with DCM (3×100 mL) and washed with saturated Na 2 S 2 O 3 The combined organic phases were washed with aqueous solution and water, and then with Na 2 SO4 After drying, the solvent was removed under reduced pressure. The crude product was a dark orange solid (7.56 g, 66%). The crude product was purified by silica gel column chromatography. 3.25 g of bright red pyrrole-4,5-dione (1) crystals were obtained. The yield was 27%.

[0033] 1 H NMR (300MHz, Chloroform-d): δ / ppm 8.42 (dd, J=7.4, 1.3Hz, 2H), 8.12 (dd, J=8.0, 1.3Hz, 2H), 7.79 (s, 2H), 7.71 (t, J=7.7Hz, 2H). 13 C NMR (75MHz, Chloroform-d): δ / ppm135.75,132.00,130.08,128.33,127.98,127.26.MODI-TOF-MS:m / z calculated forC 16 H 8 O 2 [M]+:232.05; found:232.09.Elemental analysis(%)for C 16 H 8 O 2 :C82.75,H 3.47,O 13.78; found:C 82.73,H 3.48,O 13.47.

[0034] Synthesis of compound M2

[0035] In a round-bottom flask, dissolve pyrene-4,5-dione (1) (2.00 g, 8.62 mmol, 1.0 eq.) in 20 ml of concentrated sulfuric acid. Add n-bromosuccinimide (2.75 g, 15.50 mmol, 1.8 eq.) and stir at 0°C for 15 minutes. Stir at room temperature for 1 hour. The reaction mixture is precipitated in 2 l of water / ice, collected by filtration, and washed with water and methanol. Then dried under high vacuum to obtain a bright yellow solid with a quantitative yield of 9,10-dibromopyrene-4,5-dione (2).

[0036] 1 H NMR (500MHz, DMSO-d6, 120℃): δ / ppm 8.72(d,J=8.3Hz,2H),8.47(d,J=7.4Hz,2H),7.98(t,J=7.9Hz,2H).Mp=360℃(decomposition).Elemental analysis(%)calculated C 16 H 6 Br2 O 2 :C 49.27, H 1.55, Br 40.97, O 8.20; Found: C 49.41, H 1.73, Br41.03, O 8.21.

[0037] Synthesis of Compound M3

[0038] 4,5-dibromobenzene-1,2-diamine (1.00 g, 3.76 mmol, 1 eq.) and (4-(diphenylamine)phenyl)boric acid (2.72 g, 9.40 mmol, 2.5 eq.), K 2 CO 3 (2.08 g, 15.04 mmol, 4 eq.) and Pd(PPh 3 ) 4 (87mg, 0.075mmol, 0.02eq.) was added to a mixture of 1,4-dioxane and water (10 / 1, v / v) in 100mL of argon. The mixture was stirred at 90°C for 24h, cooled to room temperature, poured into 100mL of water, and then extracted with dichloromethane (DCM). The obtained layer was evaporated under reduced pressure and purified by column chromatography using petroleum ether and ethyl acetate (2 / 1, v / v) as eluents. The mass of the obtained white wax solid was 1.79g, and the yield was 78%.

[0039] 1 H NMR(400MHz,Chloroform-d)δ / ppm 7.21(t,J=7.7Hz,8H),7.07(d,J=7.8Hz,8H),6.99(d,J=8.0Hz,8H),6.92(d,J=8.3Hz,4H),6.79(s,2H).13C NMR(101MHz,DMSO-d6)δ147.27,144.47,137.34,134.44,130.55,129.35,128.59,123.42,123.24,122.51,115.98.MODI-TOF-MS:m / z calculated for C 42 H 34 N 4 [M] + :594.76; found:594.15.Elemental analysis(%)for C 42 H 34 N 4 :C 84.82, H 5.76, N 9.42; found: C 84.79, H5.63, N 9.41.

[0040] Synthesis of compound M4

[0041] 9,10-Dibromopyridine-4,5-dione (2) (700 mg, 0.74 mmol, 1 eq.), N4,N4,N4″,N4″-tetraphenyl-[1,1':2',1″-terphenyl]-4,4',4″,5'-tetraamine (3) (443 mg, 0.74 mmol, 1 eq.) were added to 70 mL AcOH and 5 mL EtOH under argon. The mixture was stirred at 85°C for 16 h, cooled to room temperature, and mixed with ice water. The resulting mixture was filtered under reduced pressure and recrystallized to obtain a yellow solid containing 530 mg, with a yield of 75%.

[0042] 1 H NMR(400MHz,Chloroform-d)δ9.57(d,J=24.9Hz,2H),8.69(d,J=27.4Hz,2H),8.42–8.32(m,2H),8.09(d, J=34.8Hz,2H),7.29(d,J=7.7Hz,10H),7.23(s,4H),7.15(d,J=7.9Hz,8H),7.06(s,6H).MODI-TOF-MS:m / z calculated for C 58 H 36 Br 2 N 4 [M]+:948.13; found:948.11.Elemental analysis(%)for C 58 H 36 Br 2 N 4 :C 73.43, H 3.82, Br16.84, N 5.91; found: C 73.33, H 3.85, Br 16.90, N 5.93.

[0043] Synthesis of Compound M5

[0044] N4,N4,N4″,N4″-tetraphenyl-[1,1':2',1″-terphenyl]-4,4',4″,5'-tetraamine (3) (522 mg, 0.88 mmol, 1 eq.) and 3,6-dibromophenanthrene-9,10-dione (820 mg, 0.88 mmol, 1 eq.) were added to 70 mL AcOH and 5 mL EtOH under argon. The mixture was stirred at 85°C for 16 h, cooled to room temperature, and mixed with ice water. The resulting mixture was filtered under reduced pressure and recrystallized to obtain a yellow solid containing 653 mg, with a yield of 80%.

[0045] 1H NMR(400MHz,Chloroform-d)δ / ppm 9.15(d,J=8.5Hz,2H),8.51(s,2H),8.27(s,2H),7.81(d,J=8.5Hz,2H),7.32–7.26(m,8H ),7.20(d,J=8.1Hz,4H),7.14(d,J=7.7Hz,8H),7.04(d,J=8.0Hz,8H).MODI-TOF-MS:m / z calculated for C 56 H 36 Br 2 N 4 [M]+:924.74; found:924.43.Elemental analysis(%)for C 56 H 36 Br 2 N 4 :C 72.74, H 3.92, Br17.28, N 6.06; found: C 72.69, H 4.01, Br 17.30, N 6.00.

[0046] Synthesis of compound TPA-PyQl-BzCNT

[0047] 4,4'-(4,5-dibromophenylthro[4,5-abc]phenazine-11,12-diyl)(N,N-diphenylaniline)(4)(0.50 g, 0.53 mmol, 1 eq.), (4-cyanophenyl)boronic acid (0.17 g, 1.16 mmol, 2.2 eq.) and K were added to 80 mL NMP. 2 CO 3 (0.58 g, 4.42 mmol, 8 eq.). Then Pd(PPh3)4 (36 mg, 0.032 mmol, 0.06 eq.) was added in a nitrogen atmosphere. After the solution was heated at 130°C for 24 hours, the reaction mixture was cooled to room temperature. The product was poured into 100 mL of water and then extracted with dichloromethane (DCM). After evaporation of the organic layer, column chromatography was performed with dichloromethane / n-hexane as the eluent to obtain 0.28 g of an orange solid. The yield was 53%.

[0048] 1H NMR(400MHz,Chloroform-d)δ9.68(d,J=8.2Hz,2H),8.43(s,2H),8.01(t,J=7.9Hz,2H),7.77(d,J=8.5Hz,2H),7.66(d,J= 7.9Hz,4H),7.39(d,J=8.0Hz,4H),7.29(t,J=7.8Hz,8H),7.23(d,J=8.5Hz,4H),7.15(d,J=7.9Hz,8H),7.11–7.01(m,8H). 13 C NMR (101 MHz, CDCl 3 )δ147.56,147.26,143.77,141.91,136.01,132.06,131.80,130.89,129.39,128.15,127.38,124.93,124.70,123.21,122.64,111.59.The carbon peak isnot complete due to solubility relation.MODI-TOF-MS:m / z calculated for C 72 H 44 N 6 [M]+:992.36; found:993.08.Elemental analysis(%)for C 72 H 44 N 6 :C 87.07, H 4.47, N8.46; found: C 87.01, H 4.51, N 8.44.

[0049] Synthesis of Compound TPA-PhTh-BzCN

[0050] 4,4′-(3,6-dibromodibenzo[a,c]phenazine-11,12-diyl)(N,N-diphenylaniline)(5)(0.45 g, 0.49 mmol, 1 eq.), (4-cyanophenyl)boronic acid (0.16 g, 1.09 mmol, 2.2 eq.) and K 2 CO 3(0.20 g, 1.45 mmol, 3 eq.) was added to a mixture of 80 mL toluene, ether and water (8 / 1 / 1, v / v). Then Pd(PPh3)4 (17 mg, 0.015 mmol, 0.03 eq.) was added in a nitrogen atmosphere. After the solution was heated at 98 ° C for 24 hours, the reaction mixture was cooled to room temperature. The product was poured into 100 mL of water and then extracted with dichloromethane (DCM). After evaporation of the organic layer, column chromatography was performed with dichloromethane / n-hexane as the eluent to obtain 0.37 g of an orange solid. The yield was 78%.

[0051] 1 H NMR(400MHz,Chloroform-d)δ9.52(d,J=8.4Hz,2H),8.77(d,J=1.7Hz,2H),8.38(s,2H),7.99(d,J=8.3Hz,2H),7.93(d,J=8 .1Hz,4H),7.86(d,J=8.1Hz,4H),7.30(d,J=7.9Hz,8H),7.22(d,J=8.4Hz,4H),7.15(d,J=7.9Hz,8H),7.06(t,J=7.7Hz,8H). 13 C NMR (101 MHz, CDCl 3 )δ146.52,131.83,130.98,129.80,128.34,127.22,123.63,122.15.The carbon peak is not complete due to solubility relation.MODI-TOF-MS:m / z calculated for C 70 H 44 N 6 [M]+:968.36; found:969.79.Elemental analysis(%)for C 70 H 44 N 6 :C 86.75, H 4.58, N 8.67; found: C 86.77, H 4.61, N 8.62.

[0052] Example 2: UV and PL testing of TADF luminescent materials TPA-PyQl-BzCNT and TPA-PhTh-BzCN

[0053] The ultraviolet-visible (UV / Vis) absorption and photoluminescence (PL) spectra of these emitters in toluene solutions at room temperature are shown in Figure 1 and 2As shown. The strong high-energy absorption bands in the lower wavelength region before 400nm can be attributed to n-π* and π-π* transitions. The weaker broad absorption bands in the range of 400-550nm are caused by the transition of ICT from donor to acceptor. In toluene solution, these emitters exhibit different ICT emissions and less structured PL spectra under photoexcitation, with maxima ranging from 557nm to 545nm. Compared with TPA-PhTh-BzCN and TPA-PyQl-BzCN, the PL spectrum of TPA-PyQl-BzCN shows a significant blue shift, indicating that its ICT characteristics are weaker. Compared with TPA-PyQl-BzCN, TPA-PhTh-BzCN also exhibits obvious red-shifted emission, which is due to the addition of strong electron accepting units and more delocalized π orbitals, which enhance their ICT states. This is a common phenomenon for most organic DA molecules.

[0054] Example 3: CV test of TADF luminescent materials TPA-PyQl-BzCNT and TPA-PhTh-BzCN

[0055] Figure 4 Taking ferrocene as reference, TPA-PhTh-BzCN and TPA-PyQl-BzCN in CH 2 Cl 2 and CH 3 Cyclic voltammetry curves in CN solution. In the anodic scan, the oxidation potential peak of TPA-PhTh-BzCN is 1.079V, and the oxidation potential peak of TPA-PyQl-BzCN is 1.075V. Among them, the two TADF compounds show very similar oxidation potentials. The HOMO energy level (EHOMO) and LUMO energy level (ELUMO) of TPA-PhTh-BzCN are calculated to be -5.29 / -3.04eV and -5.28 / -2.91eV, respectively. It is observed that TPA-PhTh-BzCN and TPA-PyQl-BzCN have similar energy gaps, which is mainly due to the similar DA electron cloud distribution.

[0056] Example 4: Theoretical calculation based on TADF luminescent materials TPA-PyQl-BzCNT and TPA-PhTh-BzCN

[0057] Density functional theory (DFT) calculations were performed on these compounds at the B3LYP / 6-31G basis level to explore their geometry and electronic distribution. Figure 5As shown in the figure, the dihedral angles θ1 between the TPA part and the rigid conjugated π-bridge of the optimized TPA-PhTh-BzCN and TPA-PyQl-BzCN are 48.23° and 45.41°, respectively. In general, the HOMO and LUMO distributions of typical TADF molecules with a dihedral angle close to 90° between the donor and the acceptor are almost completely separated, resulting in a smaller oscillation intensity (f). The dihedral angles of TPA-PhTh-BzCN and TPA-PyQl-BzCN are relatively small (about 45°). This is conducive to a moderate overlap between the HOMO and LUMO, thereby increasing f. Here we observe that the LUMO of the acceptor triphenyl in TPA-PhTh-BzCN is not distributed on the strong acceptor unit after being connected to the conjugated π-bridge, which is why TPA-PyQl-BzCN has a slight blue shift compared to TPA-PhTh-BzCN, which is mainly due to the large torsion angle (θ1) between the conjugated π-bridge and the A unit. 2 ). The torsion angle of TPA-PyQl-BzCN increased from 37.74° to 66.88° relative to TPA-PhTh-BzCN, and the torsion angle almost doubled, so that the electron cloud distribution was completely separated. This complete separation of HOMO-LUMO drives the reduction of ΔEST (0.17 eV and 0.24 eV for TPA-PhTh-BzCN and TPA-PyQl-BzCN, respectively), which is conducive to an efficient RISC process;

[0058] In further experiments, the root mean square deviation (RMSD) of the conformational changes of the ground state (S0) and excited state (S1) were calculated based on the optimized molecular geometry. Significantly higher than TPA-PyQl-BzCN The higher the RMSD, the better the S 0 and S 1 The greater the conformational change between them, the more non-radiative transition channels the excited state molecules will have.

[0059] The excited state properties were further evaluated by natural transition orbital (NTO) and spin-orbit coupling matrix (SOC) studies using time-dependent density functional theory. The ground state S0 / S1 transition represents a charge transfer (CT) transition from the TPA donor to the conjugated aromatic ring acceptor. Interestingly, the lower triplet states (T1 and T2) of both compounds exhibited mixed charge transfer with charge transfer and local excitation (LE) features, which is critical for enhancing the RISC process via non-adiabatic coupling. These results suggest that the two molecules constructed from the same unit cells exhibit potential as TADF materials.

[0060] In addition, Figure 5We found that after TPA-PyQl-BzCN increased the conjugated bridge area of ​​TPA-PhTh-BzCN, the SOC between S0, T1 and T2 increased significantly, which also led to the k RISC faster than TPA-PhTh-BzCN. Surprisingly, TPA-PyQl-BzCN involves hRISC process, which is not observed in TPA-PhTh-BzCN, and the increase of surface conjugation stiffness allows the diversification of RISC process channels. Not only that, the oscillator strength of TPA-PyQl-BzCN (0.3272) is also improved compared with TPA-PhTh-BzCN (0.3153). At the same time, the reorganization energy (λ) is a reflection of S 0 State and S 1 The DA structure of the two TADF materials is similar to that of the DA structure, but the rigid skeleton is different, so the reorganization energy of the two TADF materials is the same (λ = 0.426 eV), which also shows that the introduction of the rigid skeleton does not improve the non-radiative transition behavior caused by intramolecular transition.

[0061] Example 5: Low-temperature fluorescence phosphorescence test and delayed fluorescence lifetime test based on TADF luminescent materials TPA-PyQl-BzCNT and TPA-PhTh-BzCN

[0062] The singlet and triplet energies of both emitters were calculated from their fluorescence and phosphorescence, which were measured in toluene at 77 K ( Figure 6 a and d). The singlet and triplet energy gaps (ΔEST) of TPA-PhTh-BzCN and TPA-PyQl-BzCN are 0.18 and 0.20 eV, respectively; these values ​​are sufficiently small for an efficient RISC process. The broad fluorescence and phosphorescence spectra of both emitters indicate ICT-dominated singlet and triplet excited states;

[0063] To further demonstrate the emission properties of these two emitters, the temperature-dependent transient PL decays were performed by doping 10% TPA-PhTh-BzCN and TPA-PyQl-BzCN in CBP films. Figure 6 b, c, e and f). As expected, the TPA-PhTh-BzCN and TPA-PyQl-BzCN doped films exhibited a double exponential decay curve with transient (τp) and delayed (τd) lifetimes of 23.72ns / 4.77μs and 22.13ns / 2.31μs, respectively. From 100K to 300K, the proportion of the delayed component gradually increased with increasing temperature, which can be attributed to the TADF process occurring through RISC.

[0064] Example 6: Device fabrication scheme and luminescence performance test based on TADF luminescent materials TPA-PyQl-BzCNT and TPA-PhTh-BzCN

[0065] To further verify our theory, solution-processed OLEDs were prepared using an ITO / PEDOT device structure: PSS (35 nm) / PVK (30 nm) / EML (35 nm) / TmPyPB (45 nm) / liff (0.5 nm) / Al (120 nm). Here, the EML is composed of 4,4'-bis (n-carbazolyl) -1,1'-biphenyl (CBP) and TPA-PhTh-BzCN and TPA-PyQl-BzCN. Each OLED adopts an optimal doping concentration of 10 wt%, as shown in Figure 7 As shown;

[0066] The current efficiency of TPA-PhTh-BzCN doped with 10% CBP at 584nm is 11.52cdA -1 , power efficiency is 4.76lmW -1 , EQE is 4.76%, while the current efficiency of TPA-PyQl-BzCN at 564nm is 12.01cdA -1 ,5.23lmW -1 and 7.18%. The increase in the EQE value of TPA-PyQl-BzCN is due to the effect of the rigid backbone strategy, and the rigid π-bridge suppresses the nonradiative transition.

[0067] As can be seen from the above, the present invention takes the problems raised in the background technology as the starting point, and starts from the aspects of material design and device preparation. We have developed two new TADF materials. Since they use the same D-segment triphenylamine (TPA) and their A segment contains the same main electron-deficient substructure as benzonitrile, their HOMO and LUMO energy levels are very similar. Under these conditions, phenanthrene and pyrene are selected as connecting bridges. By changing the conjugated area of ​​the rigid π-bridge, we can better understand the effect of the rigid conjugated bridge on the luminescent material. In photophysical measurements, they show very similar charge transfer (CT) characteristics in the emitted light, as expected. On the other hand, the TADF performance of TPA-PyQl-BzCN is significantly better than that of TPA-PhTh-BzCN. This can be attributed to the different aromatics of the entire A and conjugated area framework. Although both materials have equally excellent 3 LE state, but the increase in rigid conjugation area provides a relatively strong SOC and a smaller RMSD, indicating that k RISCFaster, fewer non-radiative transition channels, we also observed a high-position anti-interstitial crossing process after increasing the conjugation. Most importantly, the PLQY was increased from 75% to 90% by increasing the rigid conjugation area. This result gives us the opportunity to gain in-depth insight into the relationship between the conjugation area of ​​the rigid π-bridge and the molecular properties. At the same time, the rigid skeleton strategy enriches the diversity and stability of the TADF molecular structure. Therefore, this study deeply explores the luminescence mechanism of the rigid π-bridge acting on TADF materials, providing an effective guiding strategy for the development of efficient TADF materials.

[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A thermally activated delayed fluorescent material with a rigid π-bridge construction strategy, characterized in that: include: Using pyrenequinoxaline as a conjugated π bridge, connecting the cyanobenzene acceptor (A) unit and the triphenylamine (TPA) donor (D) unit, a new TADF material TPA-PyQl-BzCN with a DA molecular structure was constructed through Suzuki coupling. The specific molecular structure is shown below:

2. The use of a thermally activated delayed fluorescent material according to a rigid π-bridge construction strategy according to claim 1, characterized in that: The light-emitting layer is manufactured by using TADF light-emitting material, TPA-PyQl-BzCN as the light-emitting layer dopant, and CBP as the main material through spin coating and heating annealing process.

3. The use of a thermally activated delayed fluorescent material according to a rigid π-bridge construction strategy according to claim 2, characterized in that: A doped TADF organic electroluminescent device was prepared, and a TADF organic electroluminescent device with an emission peak of 564 nm and an EQE of 7.2% was obtained.

4. The use of a rigid π-bridge structured thermally activated delayed fluorescent material according to claim 3, characterized in that: The structure of the TADF organic electroluminescent device is: ITO / PEDOT:PSS(35nm) / PVK(30nm) / EML(35nm) / TmPyPB(45nm) / LiF(0.5nm) / Al(120nm); Among them, PVK is the hole transport layer, TmPyPB is the electron transport layer, PEDOT:PSS is the hole injection layer, EML is the light-emitting layer, which is a mixture of the guest material TPA-PyQl-BzCN and the host material (4,4'-di(9-carbazole)biphenyl), and the cathode layer is composed of lithium fluoride and aluminum.

Citation Information

Patent Citations

  • Electroluminescent material, preparation method thereof and light emitting device

    CN110240574A

  • Dicyano1H-benzo [d] anthracene-1-one thermally activated delayed fluorescent near-infrared luminescent material and application thereof

    CN118561720A